Hypertensive patient’s addiction status and its impact on systolic BP, diastolic BP, and blood sugar level - Durga Joshi; C. Vasantha Kalyani; Kusum Kumari (Tungs’ Medical Journal, 2025)
Background: Alcohol and smoking addiction affect systolic blood pressure (BP), diastolic BP (DBP), and random blood glucose (RBG) levels among healthy people. In hypertension cases, both can be life-threatening. Objectives: This study aimed to determine the prevalence of addiction and its impact on the three parameters mentioned above in individuals with hypertension from the rural and urban communities of Uttarakhand, India. Methods: This descriptive cross-sectional study included 435 people through convenience sampling. Data were collected using a structured questionnaire. Results: Out of 435 participants, 57% were male, and 55% belonged to a nuclear family. Their mean age was 53.19 years, and their mean family income was above 20,000 INR/month. Current smokers accounted for 18%, but only 14% were smoking daily. Furthermore, 30% consumed beer, wine, spirits, mahua/bungari, or any other local liquor. Systolic BP was linked to current smoking status (0.02), medical advice to quit smoking (0.04), and alcohol consumption in the last 12 months (0.03). Smoking (0.05), medical advice from any physician to quit smoking (0.03), smoking cessation advice from other people (0.002), smoking history (0.02), and alcohol consumption were significantly associated with DBP (0.05). The frequency of alcohol consumption in the last 12 months was also significantly related to blood glucose level (0.04). Conclusion: Only a few of the participants smoked. The nonsmokers, from both Uttarakhand’s urban and rural areas, fairly understood the harmful effects of smoking on health. Moreover, 8% of participants sought medical help to quit smoking. Alcohol and smoking addiction affected the BP and RBG levels.